2014
DOI: 10.1038/nature12968
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Stimulus-triggered fate conversion of somatic cells into pluripotency

Abstract: Here we report a unique cellular reprogramming phenomenon, called stimulus-triggered acquisition of pluripotency (STAP), which requires neither nuclear transfer nor the introduction of transcription factors. In STAP, strong external stimuli such as a transient low-pH stressor reprogrammed mammalian somatic cells, resulting in the generation of pluripotent cells. Through real-time imaging of STAP cells derived from purified lymphocytes, as well as gene rearrangement analysis, we found that committed somatic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
129
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(137 citation statements)
references
References 40 publications
3
129
2
3
Order By: Relevance
“…More recently in January 2014, Haruko Obokata, a young researcher in Japan published in Nature , showed stem cells can now be made quickly just by dipping blood cells into acid 25, 26 . On June 2014, Obokata agreed to retract both the papers and 2 months later Obokata’s mentor and co-author, Yoshiki Sasai, committed suicide by hanging.…”
Section: Fraud In Life Sciencesmentioning
confidence: 99%
“…More recently in January 2014, Haruko Obokata, a young researcher in Japan published in Nature , showed stem cells can now be made quickly just by dipping blood cells into acid 25, 26 . On June 2014, Obokata agreed to retract both the papers and 2 months later Obokata’s mentor and co-author, Yoshiki Sasai, committed suicide by hanging.…”
Section: Fraud In Life Sciencesmentioning
confidence: 99%
“…Experiments were performed using a transgenic mouse line harboring GFP under an Oct4 promoter ( Ohbo et al , 2003); the line is the same as that used in the previous studies ( Obokata et al , 2014a; Obokata et al , 2014b). The mouse line has been maintained in C57BL/6 background in a homozygous state.…”
Section: Resultsmentioning
confidence: 99%
“…This discovery raised the possibility that cellular reprogramming may also be induced by activating endogenous pluripotency genes under certain conditions. In two reports published in Nature by Obokata et al (2014a); Obokata et al (2014b), the authors claimed to have observed how “external stimuli such as a transient low-pH stressor reprogram somatic cells into pluripotent cells,” which they referred to as the STAP phenomenon; subsequently, however, after multiple problems were found with the handling and presentation of the data in a pattern indicative of research misconduct, both papers were retracted.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations